2020
DOI: 10.1111/cts.12808
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus Activity Affects the Sinusoidal Uptake Transporter OATP1B1 Evaluated by the Pharmacokinetics of Atorvastatin

Abstract: The present study assessed the effect of systemic lupus erythematosus (SLE) activity, a chronic and inflammatory autoimmune disease, on the sinusoidal uptake transporter OATP1B1 using atorvastatin (ATV) as a probe drug. Fifteen healthy subjects, 13 patients with controlled SLE (SLEDAI 0–4), and 12 patients with uncontrolled SLE (SLEDAI from 6 to 15), all women, were investigated. Apparent total clearance of midazolam (MDZ), a marker of CYP3A4 activity, did not vary among the three investigated groups. The cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…Overall, 64 full-text articles were assessed for eligibility, and 42 of these were excluded according to the following criteria: lack of quantitative PK data (18 studies), reviews (11 studies), preclinical studies (ten studies), and a lack of data on inflammatory biomarkers (three studies). After manual screening of reference lists of included studies, four more studies were identified, thus the final review included 26 original studies assessing the PK behavior of victim drugs [ 15 40 ] (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 64 full-text articles were assessed for eligibility, and 42 of these were excluded according to the following criteria: lack of quantitative PK data (18 studies), reviews (11 studies), preclinical studies (ten studies), and a lack of data on inflammatory biomarkers (three studies). After manual screening of reference lists of included studies, four more studies were identified, thus the final review included 26 original studies assessing the PK behavior of victim drugs [ 15 40 ] (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, only two studies were retrieved (Table 1 of the ESM) [ 39 , 40 ], and both investigated the inhibitory effect that pro-inflammatory cytokines may have on the OAPT1B1-mediated transport of statins during chronic inflammatory conditions. The first was a case-control PK study that tested the potential influence of a chronic inflammation state on the PK behavior of fluvastatin by comparing the profile of this probe drug of the hepatic sinusoidal OATP1B1 activity between 15 patients with RA and ten healthy volunteers [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations